2017
DOI: 10.1080/17518423.2017.1370502
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar pilocytic astrocytoma in childhood: Investigating the long-term impact of surgery on cognitive performance and functional outcome

Abstract: Objective: Previous studies differ regarding the long-term effects of surgically removed pediatric cerebellar pilocytic astrocytomas (CPA). Thus, the aim of this study was to investigate the long-term impact on neurocognitive and functional outcome and to analyze age as an influencing factor. Methods: Fourteen CPA patients were compared to the age norm and to a group of 14 high-achieving peers regarding cognitive functioning, health-related quality of life (HRQoL), and stress regulation. Mean follow-up time af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 26 publications
4
31
0
2
Order By: Relevance
“…The adult patients showed no signs of psychosocial difficulties and had an educational situation comparable to the general population in Sweden [ 34 ], which is also reported in other studies [ 15 , 23 ]. However, in a study by Pletschko et al [ 35 ] patients treated for cerebellar pilocytic astrocytoma showed satisfactory academic achievement, but when they were compared with high achievers (i e medical students) specific cognitive impairments became apparent. This underscores our findings in the interviews, that as much as one-third of the patients reported learning difficulties that were not dealt with in school, despite the fact that some of these difficulties had been diagnosed in neuropsychological investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The adult patients showed no signs of psychosocial difficulties and had an educational situation comparable to the general population in Sweden [ 34 ], which is also reported in other studies [ 15 , 23 ]. However, in a study by Pletschko et al [ 35 ] patients treated for cerebellar pilocytic astrocytoma showed satisfactory academic achievement, but when they were compared with high achievers (i e medical students) specific cognitive impairments became apparent. This underscores our findings in the interviews, that as much as one-third of the patients reported learning difficulties that were not dealt with in school, despite the fact that some of these difficulties had been diagnosed in neuropsychological investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the heterogeneous spectrum of pediatric LGG with respect to age, NF1 status, tumor site, and treatment, results of limited patient numbers have to be interpreted with caution for significance. 15 , 17 , 26 Analysis of neuropsychological sequelae has to implement distinct cognitive outcome variables apart from full-scale IQ score, which are essential for the quality of survival (QoS) and neuropsychological functioning, while remaining brief in execution. 28 Otherwise, smaller centers may have problems to implement full neuropsychological assessment due to restricted resources.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Survivors were found to be at risk for deficits in neuropsychological dimensions such as attention, processing speed, executive functioning, visual-spatial memory, language, and verbal short-term memory over time. 14 Although some studies proved good functional outcomes without severe quality of life (QoL) issues and few neurocognitive differences when comparing patients after treatment of cerebellar pilocytic astrocytoma to the healthy norm, 15–17 impairments were detected when comparing LGG patients to high-achieving peers 17 or their siblings. 13 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Brain tumors are the most common solid tumors in children, comprising 25% of all childhood cancers [1][2][3]. In this group, pilocytic astrocytomas (PCA) are the second most common, accounting for 21 to 23% of all pediatric brain tumors [3][4][5][6][7]. According to the NeuroSci 2021, 2 96 World Health Organization (WHO), PCA is classified as a Grade I tumor [3,8].…”
Section: Introductionmentioning
confidence: 99%